Multidimensional prognostic index in the elderly with hip or neck femur fracture - Biagio Moretti; Vito Pesce; Antonio Esposito; Angela Notarnicola; Lorenzo Moretti; Elsa Vitale (Orthopedic Reviews, 2012)
Hip  and  neck  femur fracture surgery was associated with high post-operative mortality and poor functional results. The decision-making process with regards to the elderly with hip or neck femur fractures was of great importance, requiring consideration of ethical, medico legal and economic factors in addition to the purely medical ones. An important component in the decision-making process was the precise knowledge of the expected mortality. We considered here several articles from 1 January 2002 to 31 August 2010 that identified the possible scoring system to predict mortality in the elderly undergoing hip or neck femur fracture surgery. We found seven studies which included a total of 12,177 patients that were assigned to hip/neck femur fracture surgery. Each study identified the possible scoring system to predict mortality in the elderly undergoing hip/neck femur fracture surgery. By reviewing the literature available, it was shown that there were more multidimensional prognostic indexes in the elderly after hospitalization than multidimensional prognostic indexes with hip or neck femur fracture which could be used as a simple point scoring system at the bedside to predict mortality in the elderly undergoing hip or neck femur fracture surgery. Although, all the prognostic indexes searched worked well for a general population, but they were of limited validity in the specific, relatively homogeneous population of hip/neck femur fracture patients.